Antibody Labeling with Remazol Brilliant Violet 5R, a vinylsulphonic reactive dye - Ferrari, Alejandro (2012)
Colloidal gold is the first choice for labeling antibodies to be used in Point Of Care Testing. However, there are some recent reports on a family of textile dyes—named “reactive dyes”—being suitable for protein labeling. In the present article, protein labeling conditions were optimized for Remazol Brilliant Violet 5R, and the sensitivity of the labeled antibodies was assessed and compared with that of colloidal-gold labeled antibodies. Also, the accelerated stability was explored. Optimal conditions were pH 10.95, dye:Ab molar ratio of 264 and an incubation time of 132 min. Labeled antibodies were stable, and could be successfully used in a slot blot assay, detecting as low as 400 ng/mL. Therefore, the present work demonstrates that vinylsulphonic reactive dyes can be successfully used to label antibodies, and are excellent candidates for the construction of a new generation of Point of Care Testing kits.